Oral microbes and its environment : a review article / Wan Nordini Hasnor Wan Ismail, Fathilah Abdul Razak and Zubaidah Haji Abdul Rahim - Abdul Razak, Fathilah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
The ecosystem within the oral cavity is unique as it is a result of interactions between components such as the oral fluids and oral microorganisms with structures of the oral soft and hard tissues. The soft structures are represented by the mucous membranes while the hard surface is represented by the teeth. Both the soft and hard tissue structures influence the distribution of microbes in the mouth. Some surfaces like those at the gingival junction protect their microbial inhabitants from any physical forces or/and chemical interactions, whereas other surfaces like the lingual incisal surface do not. Thus, the oral cavity represents a host environment that possessed features that support the establishment and growth of a great diversity of microbes. The cheek mucosa, the tongue, the gingival crevice and the tooth surface provide sites with different physicochemical and nutritional microenvironment that allows for the adherence and growth of selective microorganisms.